Going From an Academic Medical Center to a Community Hospital: Patient Experiences with TransfersGoing from an academic medical center to a community hospital: Patient experiences with transfers - Alexander Kazberouk; Nicole Boyd; Sandra Oreper; Michael Chang; James Harrison; Priya Prasad; Ari Hoffman (The Beryl Institute, 2022)
Academic medical centers (AMCs) often operate at or near full capacity, which leads to delays in care while smaller community hospitals may have excess capacity. To address this issue and to match patient needs to care acuity, patients may be transferred from an AMC emergency department for direct admission to a community hospital. We aimed to explore the experiences and perspectives of patients who were transferred. We randomly selected patients transferred between February 2019 and February 2020. We conducted structured thirty-minute interviews containing fixed response and open-ended questions focusing on the transfer rationale and experience, care quality, and patient financial outcomes. We used descriptive statistics to summarize questions with fixed responses and thematic analysis for open-ended questions. We interviewed a total of 40 patients. While most (88%) understood the rationale for transfer, many (60%) did not feel they had agency in the decision despite the voluntary nature of the program. Patients generally had a positive experience with the transfer (65%) and valued the expedited admission. However, some highlighted issues with transfer-related billing and the mismatch between the expectations of presenting to an academic hospital and the reality of being admitted to a community one. We conclude that patients are amenable to transfers for an expedited admission and understand the rationale for such transfers. However, participants should receive a clear explanation of benefits to them, guidance that the program is voluntary, and protection from financial risk Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.